Development and initial testing of an autonomous surface vehicle for shallow water mapping - Mat Idris, Mohamad Hilmi; Sahalan, Muhammad Irsyad; Abdullah, M. A.; Zainal Abidin, Zulkifli (Asian Research Publishing Network (ARPN), 2015)
Current technology offers variety of methods for underwater mapping a.k.a. bathymetry where Autonomous Surface Vehicle (ASV) is used to complement the weakness of other bathymetry approach. In initializing the design of AquaDrone ASV, it started from deciding the specification of the ASV to draw a guideline of the prototype limit. The hull of the ASV was the first to be taken into consideration due to the measure of the vessel’s payload and stability. It was built with dual control modes which are the autonomous and the tele-operated mode with Global Positioning System (GPS) receiver and compass module to assist its localization and navigation. The ASV was then tested at swimming pool, ponds and lakes to analyze its performance on maneuvering, sensors fusion, data logging, and communication range. It was proved to be operational.